Briga de vizinhos: um estudo dos processos de constituição da escola pública de instrução primária na província paulista (1853 - 1889) - Barra, Valdeniza Maria Lopes da (2005)
The text presented here is a result of the research carried through in the Public Archive of the State of São Paulo, whose basic documentary corpus is constituted by processes that had happened on professors of primary instruction s public school in São Paulo s Province between the years of 1853 and 1889. The reading of this material implied in the search and the crossing with other documents, among which, stand out the acts registered in annals of the Assemblies, the debates occurred in the period previous to the publication of the instruction s normative texts, the proper normative texts (laws and regulations) and the consultation of newspapers of circulation at that time. Such procedures had allowed the best agreement of the object school seen under the perspective of the relation between the institution of the school inspection s public service, the mechanisms of control given by the normative disposal of the pair infraction and penalty (in the relation with the professor s service) and the relations between the school, its direct and indirect agents, including students, professors, students parents, neighbors, authorities of local influence and authorities of the Public Instruction s service. The concepts of culture and school form constitute analysis tools that had helped in the clearence of important aspects of the contradictions put by the imposition of making school when this still was a novelty to the agents more and less direct with the task of its accomplishment, evidencing the questions that had contributed in the clearence of tensions between some of the dimensions between the public and the private one, the oral and the writing, among others.